Frequency of Development of Atrial Fibrillation After Coronary Artery Bypass Grafting in Different Age Groups : Frequency of Development of Atrial Fibrillation - Ali Khahro, Adnan; Farhan Khan, Muhammad; Aslam, Sana; Iqbal Dar, Mudassir; Aurooj, Hafsa; Bai, Veena (Pakistan Journal of Health Sciences, 2023)
Atrial fibrillation is a known complication in patients having coronary artery bypass grafting (CABG) surgery with a Post- up to 32% after CABG reported incidence up to 32%. Objective: To determine the frequency of development of atrial fibrillation after coronary artery bypass grafting surgery in different age groups. Methods: This was an observational prospective cross sectional study, conducted at department of cardiac surgery Dr Ruth.K.M.Pfau Civil Hospital Karachi. The sample size of 199 was calculated. All patients between the ages of 30-70years. Irrespective of gender, refer for CABG surgery was included in the study. Two groups were made on the basis of their age, group 1, 30-50 years and group 2, 51-70 years. Those patients who came for CABG along with valve replacement and or other concomitant surgery were not included in my study. Results: After data collection through Performa data analyzed on SPSS 17.0. As per results 20.1% individuals in the study developed atrial fibrillation. Male to female ratio was 3: 1. In Group 1, 16.6% patients developed Atrial Fibrillation and in group 2 21.58% developed Atrial Fibrillation with p value of 0.85. Hypertension was a commonest co-morbid and present in 56.2% patients in this study. Conclusion: The study concluded that the frequency of development of atrial fibrillation after CABG as 20.10 %. Patients with positive family history of coronary artery diseases and smokers have significantly higher risk to develop atrial fibrillation after surgery.